Monitoring Social and Economic Impacts of COVID-19 on Refugees in Uganda : Results from the High-Frequency Phone Survey - Second Round - World Bank (World Bank, Washington, DC, 2021)
The High-Frequency Phone Survey for refugees in Uganda (URHFPS) tracks the socioeconomic impacts of the COVID-19 crisis on refugees. The World Bank (WB) in collaboration with the Uganda Bureau of Statistics (UBOS) and the United Nations High Commissioner for Refugees (UNHCR) launched and conducted the URHFPS. The URHFPS tracks the impacts of the pandemic on a monthly basis for a period of three months. Data collection for the first round of the URHFPS took place between October 22- November 25, 2020. Data collection for the second round of the URHFPS took place between December 5-24, 2020. This brief discusses results from the second round of the URHFPS. Where possible and appropriate, results are compared across the two rounds. Detailed results from the first round are available in Atamanov et al. (2021).